Tolerance is an Important Factor of International Harmony (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The traditions, which are the mirror of every nation, contain the total material and spiritual wealth of the nation: traditions, history, language, culture, social, economic, and political life, and are enriched by the achievements of other nations' values. .As Uzbekistan is a multi-ethnic country, harmonizing the interests of different nationalities and ensuring harmony between them is considered as one of the decisive factors of development. Today, the international community has recognized and acknowledged that the principles of international tolerance are fully observed in our country.